A linguagem da violência nos contos de Famílias terrivelmente felizes de Marçal Aquino - Mendes, Fábio Marques [UNESP] (2014)
The critical analysis of Famílias terrivelmente felizes (2003) short stories, by Marçal Aquino, aims at identifying the use that the author makes of a violence language that pervades the articulation of themes and motifs, the constitution of narrators, the characterization of characters, and the materiality of texts. In regard to content, this violence is adjusted, either predominantly or incidentally, to images of physical, psychological, social, and symbolical death, features of an authoritarian Brazilian society and raw material for the production line of a new realism present in contemporary Brazilian fiction. Therefore, the role of this language is ambiguous, thanks to the ironic happening, with its action marked by subtlety, but also being completely perverse, installing itself in the intimate life of irony interpreters that experience the emptying of public space in the Brazilian social and political post-military regime period. In these terms, national symbols related to family metaphor are questioned by Aquino’s short stories, such as to that represented by the supranational family, the Nation-state, and the one represented by the ideal model of bourgeois family